Income Convergence : Fresh Evidence from the Nordic Countries - Liew, Venus Khim-Sen; Ahmad, Yusuf (2012)
Using the recently developed linearity test and nonlinear unit root test, this study shows that the income gaps of Finland, Norway, and Sweden with respect to Denmark are nonlinear but stationary with no significant trend effect, implying the Nordic countries have already attained steady state of income equality, a state beyond catching up as identified earlier in Oxley and Gresley (1999). This fresh evidence strengthens the finding of Nordic Convergence Club by these authors.